Comparative Error Analysis on Spoken Production Made by Students of the Second and the Fourth Semester of English Education Department of Muhammadiyah University of Surakarta - Kafifah, Nur; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph. D. (2016)
This present study deals with the comparative analysis of spoken production errors made by the 2nd and the 4th semester students of Department English Education of Muhammadiyah University of Surakarta. The objectives of this research are to identify the types of errors, the frequency of error, the dominant type of errors, the similarities and differences of errors, and the sources of errors made by the 2nd and the 4th semester students. The type of this research is qualitative research. The data of this research are utterances containing errors taken from the 2nd and the 4th semester students. In collecting data, the researcher listens to the audio record carefully, writes the scripts of the audios, then identifies the data, and selects the data deals with the types of errors. The researcher uses the theory of Clark and Clark, Dulay, Burt, and Krashen to analyze the errors. The results indicate that there are three types of errors made by the 2nd semester students namely, speech errors (78,22%), morphological errors (15,6%), and syntactical errors (6,06%). Whereas, the erroneous made by the 4th semester students are speech errors (83,86%), morphological errors (13,1%), and syntactical errors (2,93%). The speech errors made by the 2nd and the 4th semester students have the similarities and differences. The similarities of speech errors that found by the researcher are: silent pause, filled pause, repeats, false start (unretraced), false start (retraced), correction, interjection, stutters, slip of tongue, error in pronunciation, error in vocabulary, error in word selection, the omission of bound morpheme-s, omission of to be, addition of to be, omission of verb, omission of -Ing, addition of -Ing, and misuse of to be. The differences of errors made by the 2nd and the 4th semester students are in the addition of preposition, misformation, and misordering. The dominant error made by students is filled pause. The speech errors are mostly caused by three sources; they are cognitive difficulty, situational anxiety, and social reason.